2016
DOI: 10.1111/ina.12310
|View full text |Cite
|
Sign up to set email alerts
|

Airborne particle emission of a commercial 3D printer: the effect of filament material and printing temperature

Abstract: The knowledge of exposure to the airborne particle emitted from three-dimensional (3D) printing activities is becoming a crucial issue due to the relevant spreading of such devices in recent years. To this end, a low-cost desktop 3D printer based on fused deposition modeling (FDM) principle was used. Particle number, alveolar-deposited surface area, and mass concentrations were measured continuously during printing processes to evaluate particle emission rates (ERs) and factors. Particle number distribution me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
144
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(153 citation statements)
references
References 60 publications
8
144
1
Order By: Relevance
“…Real‐time instruments that measure total particle number concentration from 20 nm to 1 μm (P‐Trak, Model 8525, TSI Inc., Shoreview, MN), size distribution of particles from 5.6 to 560 nm (fast mobility particle sizer [FMPS], Model 3091, TSI Inc.), and size distribution of particles from 0.5 to 20 μm (aerodynamic particle sizer [APS], Model 3321, TSI Inc.) were used to monitor chamber air before, during, and after printing. The P‐Trak and FMPS were used to monitor for the presence of particles smaller than 1 μm which has been the focus for FDM™ printers using base polymer filaments in prior studies . The APS was used to evaluate the release of particles with sizes greater than the upper cutoffs of the P‐Trak and FMPS during printing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Real‐time instruments that measure total particle number concentration from 20 nm to 1 μm (P‐Trak, Model 8525, TSI Inc., Shoreview, MN), size distribution of particles from 5.6 to 560 nm (fast mobility particle sizer [FMPS], Model 3091, TSI Inc.), and size distribution of particles from 0.5 to 20 μm (aerodynamic particle sizer [APS], Model 3321, TSI Inc.) were used to monitor chamber air before, during, and after printing. The P‐Trak and FMPS were used to monitor for the presence of particles smaller than 1 μm which has been the focus for FDM™ printers using base polymer filaments in prior studies . The APS was used to evaluate the release of particles with sizes greater than the upper cutoffs of the P‐Trak and FMPS during printing.…”
Section: Methodsmentioning
confidence: 99%
“…Several filament polymers are available for use in desktop 3‐D printers, including, but not limited to, acrylonitrile butadiene styrene (ABS), polylactic acid (PLA), and polycarbonate (PC). Thermal degradation of polymer filaments during 3‐D printing has been shown to release millions to billions of ultrafine particles (UFP) per minute and numerous organic chemicals into air …”
Section: Introductionmentioning
confidence: 99%
“…In particular, the ability of UFPs to easily cross the biological barriers and their greater biological activity were recognized as their main characteristics leading to harmful health consequences [6,7,8,9,10,11]. Therefore, several studies have recently been conducted to quantify and characterize UFP emissions from different sources and their distribution in the environment [12,13,14,15,16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…Factors such as particle size, morphology, type of particle (agglomerate and aggregate), particle composition, concentration, and instrument configuration can affect accuracy. NanoScan has shown overestimation or deviation in some studies, while in other studies, it has shown good comparability to other types of SMPS . Several reasons for this overestimation have been suggested, including breakup of weak agglomerates at the inlet cyclone, use of unipolar corona charge, and pre‐existing charges .…”
Section: Discussionmentioning
confidence: 99%
“…6,10,12 When printing at temperatures lower than the manufacturer's recommendations, particle emissions are relatively low or at negligible levels, whereas significant emission rates have been measured at temperatures higher than the manufacturer-recommended level. 9,21 Previous research studies have examined the effect of temperature under a few conditions, but it has not been systematically evaluated. 9,10,12,18,21,22 These studies provided characterizations of particle emissions under limited conditions and did not attempt to estimate the emission rates stage by stage at various temperature.…”
mentioning
confidence: 99%